Morphology of mouse seminiferous tubules - Nakata, Hiroki (Anatomical science international, 2019)
We developed a technique to analyze the high-resolution three-dimensional (3D) structure of seminiferous tubules. It consists of segmentation of tubules in serial paraffin sections of the testis by marking the basement membrane with periodic acid–Schiff or a fluorescent anti-laminin antibody followed by 3D reconstruction of tubules with high-performance software. Using this method, we analyzed testes from mice at different ages and accurately elucidated the 3D structure of seminiferous tubules, including the number and length of tubules as well as the numbers of connections with the rete testis, branching points, and blind ends. We also developed a technique to identify the precise spermatogenic stage and cellular composition of the seminiferous epithelium. It consists of the combination of lectin histochemistry for acrosomes and immunohistochemistry for specific cell markers visualized with fluorescence. Using this method, we examined seminiferous tubules from normal mice and counted the number of each cell type at each stage, and thereby established a quantitative standard for the cellular composition of the seminiferous epithelium. We then investigated seminiferous epithelia from genetically modified infertile mice deficient in certain cell adhesion molecules and revealed characteristic abnormalities in the cellular composition. We also analyzed the distribution and direction of spermatogenic waves along the length of adult seminiferous tubules as well as the site of the first onset of spermatogenesis in postnatal seminiferous tubules. These methods will be useful for investigating the structure and function of seminiferous tubules in mice and humans under normal and pathological conditions.